Clinical evaluation of photoprotective effect by a topical antioxidants combination (tocopherols and tocotrienols) - Pedrelli, V.F.; Lauriola, M.M.; Pigatto, P.D. (Journal of the European Academy of Dermatology and Venereology, 2012)
Background  Vitamin E is among the earliest recognized antioxidants. Recent findings suggested that tocotrienols have superior activity than tocopherols. Moreover, vitamin A is well‐known in dermatology for its actions, including the ultraviolet radiation absorbing property. Objectives  In view of experimental evidence for the photoprotective properties of these antioxidants, we evaluated in 30 patients with photosensitivity, the prophylactic efficacy of a new topical agent, containing tocopherols 10% and tocotrienols 0.3%, compared with retinol, simple vehicle and untreated areas. Methods  After determination of the minimal UVB erythema dose (MED), two areas of 2 × 2 cm were selected on the buttocks of each subject, one of which was treated with the antioxidant formulation whereas the other field did not undergo any treatment. Therefore, both areas were irradiated with a twofold MED. As further controls, other two similar areas, selected on the forearm of 15 patients, were photo‐irradiated similarly, 30 min after application of the simple vehicle to a field and of vitamin A in the same vehicle to the other. Reactions (erythema/oedema/itch/vesciculation) assessment was carried out assigning scores indicative of their intensity; then, mean values +DS of scores were calculated. Results  The pre‐treatment with the vitamin E formulation highly protects against photosensitivity, and all reactions to irradiation were significantly lower in the areas treated with the topical vitamin E formulation compared to those treated with the simple vehicle or vitamin A. Conclusions  The use of a new topical formulation containing significant concentrations of tocotrienols and tocopherols represents a promising strategy to reduce the photo‐induced skin damage.